The The Effect of Firm Size, Growth Opportunity and Net Working Capital on Cash Holding in Main Board Healthcare Sector Companies Listed on The Indonesia Stock Exchange - Yanti Zalsabila; Nuramal; Anwar (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This research aims to test and analyze the influence of firm size, growth opportunity and net working capital on cash holding. The population used in this research is main board healthcare sector companies listed on the Indonesia Stock Exchange in 2020-2022 using a purposive sampling method, so the total sample for this research is 36 financial report data from main board healthcare companies listed on the IDX for 3 years. The analytical method used in this research is multiple linear analysis method and hypothesis testing. The results of this research show that firm size has no effect on cash holding, growth opportunity has no effect on cash holding and net working capital has a significant positive effect on cash holding.